AN EVALUATION OF LIQUEFACTION POTENTIAL IN THE REGION OF PADANG CITY - Indra Farni (Fakultas Teknik Sipil dan Perencanaan. Universitas Bung Hatta, 2021)
Padang City is a city located on the Coastline of West Sumatra Coast that is vulnerable to earthquakes and tsunamis. This vulnerability allows the liquefaction phenomenon when an earthquake occurs. Factors affecting liquefaction are soil type, grain grading, ground water level, relative density and vibration. This study aims to analyze the liquefaction potential based on the value of safety factors obtained by using the Seed et al (1985) method and the Liquefaction Potential Index (LPI) method which aims to map the liquefaction based on the level of liquefaction potential at the location being reviewed. Earthquake data is using the Indonesia meterological, climatology, and geophysics agency (BMKG) (2009-2019) and maximum ground surface acceleration (PGA) using the attenuation equation from Young et al. The liquefaction calculation parameters are judged by a safety factor (FS), if FS> 1 it means there is no potential for liquefaction and if FS <1 means there is potentially liquefaction possibility. Based on calculations from these methods, the results obtained from the ten location points reviewed were almost all sites potentially liquefaction based on variations in earthquake magnitude with sand and silt soil types and other types of soil with an average groundwater level below 1.5m.